Caries lesion remineralization with fluoride toothpastes and chlorhexidine - effects of application timing and toothpaste surfactant - Sami A. Almohefer; John A. Levon; Richard L. Gregory; George J. Eckert; Frank Lippert (University of São Paulo, 2018)
Abstract Habitual toothbrushing with fluoridated toothpaste followed by rinsing with antibacterial mouthwashes is a method to maintain good oral hygiene and to diminish the occurrence and severity of dental caries and periodontal disease. However, our understanding of how antimicrobial agents in mouthwashes affect fluoride-mediated caries lesion remineralization is still poor. Objective: The objectives of this in vitro study were a) to determine the effects of the waiting period of chlorhexidine (CHX) rinsing after fluoride toothpaste use and b) to further determine the effect of the type of toothpaste surfactant [sodium dodecyl sulfate (SDS) or cocamidopropyl betaine (CAPB)] on caries lesion remineralization associated with CHX rinsing. Material and Methods: Caries lesions were formed in bovine enamel specimens and assigned to 10 treatment groups (n=18) based on Vickers surface microhardness (VHN). Lesions were then pH-cycled for 10 days with daily regimen comprised of twice daily toothpaste slurry treatments (1150 ppm fluoride, with SDS or CAPB), followed by CHX solution treatments [0, 15, 30 or 60 minutes following slurry treatment or no CHX treatment (negative control)]. VHN was measured again and the extent of lesion remineralization calculated (∆VHN). Results: ∆VHN with SDS-toothpaste was significantly lower than with CAPB-toothpaste, indicating more remineralization for the CAPB-toothpaste. ∆VHN with 0-minute waiting time was significantly lower than with 30-minute waiting time and with negative control. Conclusions: The absence of CHX as an adjunct to fluoride toothpastes led to greater remineralization of enamel lesions compared with the immediate use of CHX treatment for both SDS- and CAPB-toothpastes. CAPB-toothpastes indicated significantly greater remineralization than SDS-toothpastes, and can be suggested for patients at high risk of caries. A 30-minute waiting time for CHX treatment is recommended after brushing.